P070 Can familiar sensory inputs reduce the first night effect when sleeping in an unfamiliar hotel room?. (19th November 2019) - Earl, Victoria; Stratton, Mark; Guo, Jonathan; Kim, Chang; Morrell, Mary
Abstract : Introduction: The first night effect (FNE) is the phenomenon of reduced sleep quality during the first night in a new environment. It is hypothesised that this is due to asymmetrical levels of activity in the two hemispheres of the brain to remain more vigilant. We aimed to determine whether the first night's stay in a hotel led to a reduction in sleep quality, and whether this could be mitigated by using one's own pillowcase. Methods: Participants were recruited with ethical approval via a questionnaire including a list of exclusion criteria. Participants then spent one night in the hotel room, followed by four nights at home. During the hotel stay the 'control group' used the hotel pillowcase and the 'intervention group' used their own pillowcase. Sleep quality was self-reported using a visual analogue scale, which was then converted into numerical data. Sleep quality at the hotel was compared to the mean quality at home. Additionally, hotel sleep quality was compared between the control and intervention groups. All data was analysed using a paired two-tailed t-test. Results: Sixteen participants (Mean age 20.3 (±1.2) years; 10 female, 6 male) completed the study. During the hotel stay, mean sleep quality in the control group was 54.6 (AU) compared to 46.3 in the intervention group. Sleep quality of the control group increased from 54.6 in the hotel to 66.2 at home. No observed differences were statistically significant. Discussion: Overall, no statistically significant evidence was found to support the presence of the FNE in hotels or that use of one's own pillowcase reduces the FNE. However, there is still potential to build upon this research as this is an understudied area and applications in business and wellbeing. Acknowledgments: Thanks to Tom Hupe of Perkins+Will and Hilton London Metropole for supporting this project.